PROFESSIONAL ADAPTATION OF MILITARY PERSONNEL TO CIVILIAN LIFE IN UKRAINE: HISTORY AND PRESENT (Innovative professional education, 2024)
The Russian-Ukrainian war led to the creation of a class of veterans in Ukraine who need integration into civilian life. Rehabilitation of ex-servicemen involves professional adaptation, which creates additional pressure on the state and society as a whole. This aspect involves increasing the competence of social workers and teachers receiving education in specialized institutions, as they must have sufficient competence to work with war veterans.
Keywords: rehabilitation, ex-servicemen, professional adaptation